Extraction of polysaccharide from Spirulina platensis - advantage of freeze-thaw method - Thi Dong Phuong, Nguyen; Van Anh, Le Thi; Thi Dieu Huong, Le; Thi My Yen, Pham (Vietnam Journal of Biotechnology, 2021)
Polysaccharide is one of the key natural products that profit human living conditions. This study aimed at investigating the polysaccharide extraction from Spirulina platensis (PSP) basing on previous research on optimization of experimental conditions. As a result, the efficiency of raw PSP for four extraction methods was 8.35%, 65%, 76.9% and 85.1% for hot water, lye, ultrasound-assisted and freeze-thaw extraction method, respectively, which was higher than previously reported results. Particularly, the efficiency of pure PSP extraction was highest with 14.89% of the dry matter of raw PSP for freezing-thawing method. To determine the major compounds constructing the pure PSP, the composition of PSP monosaccharides was determined by HPLC. The result showed that major PSP monosaccharides were glucose and galactose, of which glucose composition was up to 85%. Furthermore, pure PSP showed antioxidant activity with IC50 values of 373, 403, 276, and 258 mg/mL for hot water, lye, ultrasound-assisted, and freeze-thaw extraction method, respectively, as compared to IC50 of 101.7 mg/mL for ascorbic acid as control.